Вікові особливості обміну ліпідів і ліпопротеїнів у сироватці крові сирійських хом’ячків-самців у нормі та при застосуванні висококалорійної дієти - Черних, В.П.; Загайко, А.Л.; Вороніна, Л.М.; Стрельченко, К.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Some parameters of lipid and lipoprotein metabolism in blood serum and liver of 4 and 20 weeks aged male hamsters in the norm and under high-caloric diet are investigated. It has been shown that the lipid profile of a blood plasma is degraded with aging in males, that expresses in an increase of the contents of FFA and triglycerides and a decrease of the HDL-cholesterol level. Under the use of a high-caloric diet, atherogenic dyslipidemia, which expresses in an increase of the levels of hypertriacylglycerolemia and apo-B-lipoproteins and a decrease of the HDL-cholesterol level, develops in experimental animals irrespective of age.